2021
DOI: 10.3390/su13137196
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Analysis of Glacier Debris Flow by Investigating the Changes in Glaciers Based on Remote Sensing: A Case Study

Abstract: Glacier debris flow is one of the most critical categories of geological hazards in high-mountain regions. To reduce its potential negative effects, it needs to investigate the susceptibility of glacier debris flow. However, when evaluating the susceptibility of glacier debris flow, most research work considered the impact of existing glacier area, while ignoring the impact of changes in glacier ablation volume. In this paper, we considered the impact of the changes in the glacier ablation volume to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…As illustrated in Figure 11, the moraines caused by ice avalanches and avalanches are very likely to lead the ice floods, landslide, glacial debris flow, and other glacial disasters, which causes serious damage to the bridges, road, etc. The occurrence of glacial hazards has its spatiotemporal distribution pattern, occurrence mechanism, and disaster process (Lin et al, 2021). In general, the warming and wetting of the climate lead to the increase of glacier instability, which in turn leads to the occurrence of glacier disaster risk.…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated in Figure 11, the moraines caused by ice avalanches and avalanches are very likely to lead the ice floods, landslide, glacial debris flow, and other glacial disasters, which causes serious damage to the bridges, road, etc. The occurrence of glacial hazards has its spatiotemporal distribution pattern, occurrence mechanism, and disaster process (Lin et al, 2021). In general, the warming and wetting of the climate lead to the increase of glacier instability, which in turn leads to the occurrence of glacier disaster risk.…”
Section: Resultsmentioning
confidence: 99%
“…Among the two papers using feature weighting, the algorithms utilized were certainty factor and genetic algorithm. Among the 46 studies using model comparison, the number of papers comparing ML models (36) was significantly higher than that of those comparing ML models and non-ML models (10), as shown in Figure 8. Among the 36 papers comparing ML models, the number of papers comparing shallow ML models (32) was much higher than that of those comparing shallow ML models and deep learning models (4).…”
Section: Prediction Performance Improvement Strategiesmentioning
confidence: 96%
“…Hazard, on the other hand, incorporates triggering factors like rainfall into the susceptibility assessment. Debris flow prediction models fall into four main categories: knowledge-driven models (analytic hierarchy process [31,32], rainfall threshold method [33][34][35], geomorphic information entropy [36], etc. ), traditional statistical models (weight of evidence method [37,38], certainty factor [39,40], frequency ratio [40,41], etc.…”
Section: Introductionmentioning
confidence: 99%
“…As for the method of remote sensing image susceptibility analysis, Lin et al considered the influence of the change in glacier ablation volume and conducted a mudslide susceptibility analysis using the G217 glacier mudslide-prone trench on the Dukku Highway in Xinjiang. This study showed that accurate prediction of glacier mudslide susceptibility could be achieved using high-resolution remote sensing image data and machine learning algorithms [ 11 ].…”
Section: Introductionmentioning
confidence: 99%